2005
DOI: 10.1089/apc.2005.19.853
|View full text |Cite
|
Sign up to set email alerts
|

Sexually Transmitted Infections Among Female Sex Workers in Yunnan, China

Abstract: A cross-sectional prevalence survey of sexually transmitted infections (STIs) was conducted among female sex workers (FSWs) in Kunming, Yunnan Province, China. A total of 505 FSWs participated in the survey. All eligible participants gave informed consent. Demographic, behavioral, and clinical information of the participants was gathered by direct structured interviews. Tampon swabs were collected to test for Chlamydia trachomatis, Nesseria gonorrhoeae, and Trichomonas vaginalis and serum specimens were collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

12
102
5
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 101 publications
(120 citation statements)
references
References 23 publications
12
102
5
1
Order By: Relevance
“…The STI rate in our sample was similar to that in previous studies of FSWs in China. 13,18 Because there was no prior study that compared self-reported and biologically tested STI in FSWs in China, it is difficult to judge the extent of underreporting. However, a study conducted in drug-using FSWs in Amsterdam reported 34% underreporting of STI, 11 and a study with sexually active adolescents recruited from clinics in the United States found underreporting of STI to be 21%-47%.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The STI rate in our sample was similar to that in previous studies of FSWs in China. 13,18 Because there was no prior study that compared self-reported and biologically tested STI in FSWs in China, it is difficult to judge the extent of underreporting. However, a study conducted in drug-using FSWs in Amsterdam reported 34% underreporting of STI, 11 and a study with sexually active adolescents recruited from clinics in the United States found underreporting of STI to be 21%-47%.…”
Section: Discussionmentioning
confidence: 99%
“…However, demographic characteristics reported by our participants were similar to those observed in previous studies with different sampling methods. 13,17,18 Second, data about the history of STI testing were not available in the current study. Therefore, we could not further break down underreporting subjects into those who were tested before and those who were never tested.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations